The big book of dashboards : visualizing your data using real-world business scenarios - Wexler, Steve, 1958-; Shaffer, Jeffrey, 1972-; Cotgreave, Andy, 1972- (Hoboken, New Jersey : Wiley, 2017)
"The definitive reference book with real-world solutions you won't find anywhere else The Big Book of Dashboards presents a comprehensive reference for those tasked with building or overseeing the development of business dashboards. Comprising dozens of examples that address different industries and departments (healthcare, transportation, finance, human resources, marketing, customer service, sports, etc.) and different platforms (print, desktop, tablet, smartphone, and conference room display) The Big Book of Dashboards is the only book that matches great dashboards with real-world business scenarios. By organizing the book based on these scenarios and offering practical and effective visualization examples, The Big Book of Dashboards will be the trusted resource that you open when you need to build an effective business dashboard. In addition to the scenarios there's an entire section of the book that is devoted to addressing many practical and psychological factors you will encounter in your work. It's great to have theory and evidenced-based research at your disposal, but what will you do when somebody asks you to make your dashboard 'cooler' by adding packed bubbles and donut charts? The expert authors have a combined 30-plus years of hands-on experience helping people in hundreds of organizations build effective visualizations. They have fought many 'best practices' battles and having endured bring an uncommon empathy to help you, the reader of this book, survive and thrive in the data visualization world. A well-designed dashboard can point out risks, opportunities, and more; but common challenges and misconceptions can make your dashboard useless at best, and misleading at worst. The Big Book of Dashboards gives you the tools, guidance, and models you need to produce great dashboards that inform, enlighten, and engage"--
"In The Dashboard Book, the authors will lay out a variety of examples of successful dashboards so that the reader can find a scenario that closely matches what he or she is tasked with visualizing"--
A Strong Foundation. Data Visualization: A Primer -- The Scenarios. Course Metrics Dashboard -- Comparing Individual Performance with Peers -- What-If Analysis: Wage Increase Ramifications -- Executive Sales Dashboard -- Ranking by Now, Comparing with Then -- Are We on Pace to Reach Our Goals? -- Multiple Key Performance Metrics -- Power Plant Operations Monitoring -- Showing Year-to-Date and Year-over-Year at the Same Time -- Premier League Player Performance Metrics -- RBS 6 Nations Championship Match Performance Analysis -- Web Analytics -- Patient History Analysis of Recent Hospital Admissions -- Hospitality Dashboard for Hotel Management -- Sentiment Analysis: Showing Overall Distribution -- Showing Sentiment with Net Promoter Score -- Server Process Monitoring -- Big Mac Index -- Complaints Dashboard -- Hospital Operating Room Utilization -- Showing Rank and Magnitude -- Measuring Claims across Multiple Measures and Dimensions -- Showing Churn or Turnover -- Showing Actual versus Potential Utilization -- Health Care Provider Productivity Monitoring -- Telecom Operator Executive Dashboard -- Economy at a Glance -- Call Center -- Succeeding in the Real World. Want to Engage People? Make Your Dashboards Personal -- Visualizing Time -- Beware the Dead-End Dashboard -- The Allure of Red and Green -- The Allure of Pies and Donuts -- Clouds and Bubbles -- A Journey into the Unknown -- Glossary of Chart Types.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Dashboards (Management information systems); Organizational effectiveness -- Evaluation; Management -- Evaluation; Tableaux de bord (Gestion); x; Gestion; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Dashboards (Management information systems); Management -- Evaluation; Organizational effectiveness -- Evaluation